2021
DOI: 10.3389/feart.2021.626908
|View full text |Cite
|
Sign up to set email alerts
|

Onsite Early Prediction of PGA Using CNN With Multi-Scale and Multi-Domain P-Waves as Input

Abstract: Although convolutional neural networks (CNN) have been applied successfully to many fields, the onsite earthquake early warning by CNN remains unexplored. This study aims to predict the peak ground acceleration (PGA) of the incoming seismic waves using CNN, which is achieved by analyzing the first 3 s of P-wave data collected from a single site. Because the amplitude of P-wave data of large and small earthquakes can differ, the multi-scale input of P-wave data is proposed in this study in order to let the CNN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…EEW systems usually determine the potential earthquake damageability based on the threshold values of PGA or PGV (Fahjan et al, 2011;Hsu & Huang, 2021;Y. M. Wu et al, 2011;Zollo et al, 2010), so it is necessary to assess the effect of predicted CAV by DLcav in estimating earthquake damage.…”
Section: Threshold Test For Predicting Cavmentioning
confidence: 99%
See 2 more Smart Citations
“…EEW systems usually determine the potential earthquake damageability based on the threshold values of PGA or PGV (Fahjan et al, 2011;Hsu & Huang, 2021;Y. M. Wu et al, 2011;Zollo et al, 2010), so it is necessary to assess the effect of predicted CAV by DLcav in estimating earthquake damage.…”
Section: Threshold Test For Predicting Cavmentioning
confidence: 99%
“…EEW systems usually determine the potential earthquake damageability based on the threshold values of PGA or PGV (Fahjan et al., 2011; Hsu & Huang, 2021; Y. M. Wu et al., 2011; Zollo et al., 2010), so it is necessary to assess the effect of predicted CAV by DLcav in estimating earthquake damage. For nuclear power plants, it is proposed that incoming earthquakes would pose damaging threats when the CAV is above 0.3 g s (EPRI, 1988), and this same threshold value is used in this study to determine the damageability of incoming earthquakes.…”
Section: Generalization Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Jozinović et al 50 used seismic data from central Italy and successfully predicted PGA using the initial 7–15 s three-component seismic waves from multiple stations as inputs to CNN, indicating that this method has similar errors to the GMPE method developed by Bindi et al 26 . To fully utilize the information of initial P-waves, Hsu et al 51 proposed a method for predicting PGA by inputting P-waves into a CNN after multiscale and multidomain preprocessing and showed that the accuracy of this method exceeded that of the SVR method proposed in 2013 36 . Chiang et al 52 inputted three-component first-arrival seismic waves into a CNN to predict whether the PGA exceeded the threshold in a classified form.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many advanced methods have been proposed to estimate the magnitude and intensity of the earthquakes based on deep learning approaches. Hsu and Huang et al (2021) attempted to exploit a deep convolutional neural network (CNN) to automatically extract useful features from previously measured P-wave data without losing too much information in the seismic waveforms and successfully predict the PGA of coming earthquakes based on a single-station approach. Similarly, Chiang et al (2022) employed CNN to extract features of the initial P wave measured at a single station and predicted whether the maximum PGA of the coming earthquake of that station was larger than a pre-defined threshold.…”
Section: Introductionmentioning
confidence: 99%